Seasonal Parasitization and Carryover of Epiricania melanoleuca Fletcher, an Ectoparasite of Pyrilla perpusilla Walker, under Arid Conditions - Joshi, R K; Sharma, S K (Annals of Arid Zone, 2016)
The seasonal activity of parasitoid, under arid conditions starts on nymph pyrilla,infesting ratoon crop of sugarcane in March. The peak parasitization of adult host was observed during October. The parasitization declined in subsequent months and in December, only traces of parasitised hosts were noticed. Carryover of parasitoid was through over-wintering eggs and cocoons (Pupae).